PENGARUH METODE THINKING ALOUD PAIR PROBLEM SOLVING (TAPPS) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP NEGERI 1 MANGGAR - Suharno Suharno; Sulistiawati Sulistiawati; Samsul Arifin (Program Studi Pendidikan Matematika, Universitas Bina Bangsa Getsempena, 2019)
Mathematical communication skills are very important in mathematics learning, the reality in the field shows the mathematical communication skills of Indonesian students are still relatively low. One of the factors causing low mathematical communication skills is conventional learning. One alternative learning that can be used to improve mathematical communication skills is the TAPPS method. This study aims to investigate whether there are differences in the average mathematical communication skills of students who learn using the TAPPS method with students whose learning uses conventional learning. This research is a quantitative study with a quasi experiment method and post-test only equivalent non-group control design. The population in this study were 4 class VIII Manggar Middle School 1. The sample technique uses convenience sampling. The sample in this study were students VIII B was the experimental class and VIII A was the control class. based on data processing using the Mann-Whitney test obtained and so that it is received, it means that there is no difference in average communication skills between students who use the TAPPS method and students whose learning uses conventional learning. The average posttest results of the experimental class students were 63.7340 and the average posttest results of the control class were 53.8454. Abstrak Kemampuan komunikasi matematis sangat penting dalam pembelajaran matematika, kenyataan dilapangan menunjukan kemampuan komunikasi matemtatis siswa Indonesia masih tergolong rendah. Salah satu faktor penyebab rendahnya kemampuan komunikasi matematis adalah pembelajaran konvensional. Salah satu alternative pembelajaran yang dapat digunakan untuk meningkatkan kemampuan komunikasi matematis adalah metode TAPPS. Penelitian ini bertujuan untuk menyelidiki apakah terdapat perbedaan rata-rata kemampuan komunikasi matematis siswa yang pembelajarannya menggunakan metode TAPPS dengan siswa yang pembelajarannya menggunakan pembelajaran konvensional. Penelitian ini merupakan penelitian kuantitatif dengan metode quasi experiment dan desain non equivalent posttest only control group design. Populasi dalam penelitian ini adalah 4 kelas VIII SMP N 1 Manggar. Teknik sampel menggunkaan convenience sampling. Sampel pada penelitian ini adalah siswa VIII B merupakan kelas eksperimen dan VIII A merupakan kelas kontrol. berdasarkan pengolahan data menggunakan uji Mann-Whitney diperoleh tidak terdapat perbedaan rata-rata kemampuan komunikasi mateamtis antara siswa yang menggunakan metode TAPPS dengan siswa yang pembelajarannya menggunakan pembelajaran konvensional. Rata-rata hasil posttest siswa kelas eksperimen adalah 63,7340 dan rata-rata hasil posttest kelas kontrol adalah 53,8454.